2023
DOI: 10.3390/microorganisms11061481
|View full text |Cite
|
Sign up to set email alerts
|

Significant Microbial Changes Are Evident in the Reproductive Tract of Pregnant Rhesus Monkeys at Mid-Gestation but Their Gut Microbiome Does Not Shift until Late Gestation

Abstract: Vaginal and rectal specimens were obtained from cycling, pregnant, and nursing rhesus monkeys to assess pregnancy-related changes in the commensal bacteria in their reproductive and intestinal tracts. Using 16S rRNA gene amplicon sequencing, significant differences were found only in the vagina at mid-gestation, not in the hindgut. To verify the apparent stability in gut bacterial composition at mid-gestation, the experiment was repeated with additional monkeys, and similar results were found with both 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 121 publications
(138 reference statements)
1
0
0
Order By: Relevance
“…Some microorganisms can increase sex steroid levels through enterohepatic circulation [ 43 ], and Nuriel-Ohayon et al found that progesterone modulates the pregnancy-associated gut microbial composition [ 44 ]. We found that the serum progesterone concentration was strongly positively correlated with the abundances of the Lachnospiraceae FCS020 group and Sphingomonas, which is consistent with a previous report [ 45 ]. Additionally, the abundance of Ruminococcaceae UCG-013 was strongly correlated with the concentration of the serum 17α-hydroxyprogesterone level.…”
Section: Discussionsupporting
confidence: 93%
“…Some microorganisms can increase sex steroid levels through enterohepatic circulation [ 43 ], and Nuriel-Ohayon et al found that progesterone modulates the pregnancy-associated gut microbial composition [ 44 ]. We found that the serum progesterone concentration was strongly positively correlated with the abundances of the Lachnospiraceae FCS020 group and Sphingomonas, which is consistent with a previous report [ 45 ]. Additionally, the abundance of Ruminococcaceae UCG-013 was strongly correlated with the concentration of the serum 17α-hydroxyprogesterone level.…”
Section: Discussionsupporting
confidence: 93%